2019
DOI: 10.1103/physreve.100.052607
|View full text |Cite
|
Sign up to set email alerts
|

Two-step relaxation and the breakdown of the Stokes-Einstein relation in glass-forming liquids

Abstract: It is well known that glass-forming liquids exhibit a number of anomalous dynamical phenomena, most notably a two-step relaxation in the self-intermediate scattering function and the breakdown of the Stokes-Einstein (SE) relation, as they are cooled toward the glass transition temperature. While these phenomena are generally ascribed to dynamic heterogeneity, specifically to the presence of slow-and fast-moving particles, a quantitative elucidation of the two-step relaxation and the violation of the SE relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…Particles with a high μ i,t (in the top 25%) tend to form stringlike clusters. , This is observed for both the long-time interval t = τ α (Figure a) and short-time interval t = 0.1τ α (Figure S3a). This observation is in good agreement with our recent study based on the long-range particle group concept, where stringlike clusters were found to move cooperatively over a long time scale . To quantitatively describe the stringlike feature, we evaluate the percentage of particles that have both themselves and at least one but at most two of their neighbors belonging in the high-μ i ,τ α group.…”
supporting
confidence: 87%
See 2 more Smart Citations
“…Particles with a high μ i,t (in the top 25%) tend to form stringlike clusters. , This is observed for both the long-time interval t = τ α (Figure a) and short-time interval t = 0.1τ α (Figure S3a). This observation is in good agreement with our recent study based on the long-range particle group concept, where stringlike clusters were found to move cooperatively over a long time scale . To quantitatively describe the stringlike feature, we evaluate the percentage of particles that have both themselves and at least one but at most two of their neighbors belonging in the high-μ i ,τ α group.…”
supporting
confidence: 87%
“…This observation is in good agreement with our recent study based on the long-range particle group concept, where stringlike clusters were found to move cooperatively over a long time scale. 52 To quantitatively describe the stringlike feature, we evaluate the percentage of particles that have both themselves and at least one but at most two of their neighbors belonging in the high-μ i,τ α group. Using φ(μ) to denote this percentage of stringlike particles, which describes clusters that are strictly stringlike in shape, we find φ(μ) = 57.33%.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The Stokes–Einstein relationship is usually written as Dτ = C for supercooled liquids, where D is the self-diffusion coefficient, τ is the structural relaxation time, and C is a constant which is independent of temperature. For a Rouse chain, D ∼ N –1 and τ ∼ N 2 .…”
Section: Resultsmentioning
confidence: 80%
“…In the macroscopic thermodynamic class, these include various measures of free volume, , excess entropy, different definitions of configurational entropy, and configurational internal energy and enthalpy. , In the equilibrium structural class, ,, the length-scale-dependent pair correlation function, g ( r ), and its Fourier space analogue, the static structure factor, S ( k ), or specific scalar metrics such as the intensity of the first cage peak of S ( k ) or local aspect(s) of g ( r ) are often advocated. Surprising correlations between the alpha process and short time/distance dynamical properties have also been proposed, including the high-frequency shear modulus , and Debye–Waller factor, and in the intermediate time/length scale class the concentration of dilute mobile excitations (e.g., string length and facilitating defect concentration). Many of the proposed order parameters are difficult or impossible to uniquely define and/or experimentally measure, especially for real-world chemically complex molecules and polymers.…”
Section: Introductionmentioning
confidence: 99%